ANALISIS PRO DAN KONTRA PENERAPAN PERATURAN PEMERINTAH NO. 46 TAHUN 2013 TERHADAP USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Haviz Taufik; Eka Julianti Efris Saputri (LPPM Universitas Adiwangsa Jambi, 2021)
Tax is also the main source of state revenue, where taxes contribute more than 78% of total state income. The dominance of taxes as the main source of state revenue is no longer from the oil and gas sector, but rather focuses on tax revenues from the non-oil and gas sector because tax revenues from non-oil and gas sources will not run out or have an age limit and play a major role in national development. One of the tax revenues from the non-oil and gas sector is UMKM tax. In July 2013, the Government of Indonesia just issued a Government Regulation (PP) No. 46 which regulates the tax on Micro, Small and Medium Enterprises (UMKM). This tax aims to provide convenience to UMKM to calculate the tax due at the end of the year and is a final tax. Many pros and cons of the issuance of PP No. 46 of 2013, because there are some UMKM who feel disadvantaged and there are also those who benefit from the application of this PP. Therefore the author analyzes what are the advantages and disadvantages of applying PP No. 46 of 2013 on UMKM? After analyzing these problems, the authors concluded that the application of Government Regulation No. 46 of 2013 caused more losses than profits for UMKM because there are still many UMKM that have net profits below 8% and will pay greater taxes, Imposing Income Tax at a rate of 1% based on the amount of turnover not in accordance with the principle of income tax, not in accordance with the provisions of article 25 paragraph (7) letter c of Law No. 36 of 2008 concerning Income Tax, can trigger the emergence of jealousy from other entrepreneurs, and not in accordance with the concept of justice in taxation because it does not reflect the ability to pay.